Media Massa Melawan Teror: Analisis Framing pada Tajuk Koran Republika - Kun Wazis (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2017)
This study aims to describe the view of mass media with the Islamic ideology of Republika in response to mass shooting incident by Stephen Craig Paddock (64 years) in Las Vegas United States on Sunday (1/10/2017) which killed 59 people and injured 500 people. This research uses qualitative method with framing analysis of Robert Entman model which produces four important things. First, the editorial (header) entitled "Irony Paddock, Irony Trump" affirms the attitude of Republika who called the Las Vegas tragedy an act of terror. Secondly, Republika constructed the United States president Donald Trump as a problem because of judging Paddock's brutal action as a casual shoot, not including terrorists. Thirdly, Republika rejects the double standard of Western countries, especially the US which does not mention terrorist acts because the perpetrators are not Muslim and not black. Fourthly, Republika offers a definition of terrorism as an act involving the use or attempts of sabotage, coercion, or violence that result in the death of the population in general. This research can be used as a discourse forming critical awareness in opposing the negative views of US superpower leaders who often impose the meaning of acts of terrorism with Islam and the Muslims.Penelitian ini bertujuan mendeskripsikan pandangan media massa berideologi Islam Republika dalam menyikapi peristiwa penembakan massal oleh Stephen Craig Paddock (64 tahun) di Las Vegas Amerika Serikat, Ahad (1/10/2017) yang menewaskan 59 orang dan melukai 500 orang. Penelitian ini menggunakan metode kualitatif dengan analisis framing model Robert Entman yang menghasilkan empat hal penting. Pertama, editorial (tajuk) berjudul “Ironi Paddock, Ironi Trump” menegaskan sikap Republika yang menyebut tragedi Las Vegas sebagai aksi teror. Kedua, Republika mengontruksikan presiden Amerika Serikat (AS) Donal Trump sebagai masalah karena menilai aksi brutal Paddock sebagai  penembakan biasa, bukan termasuk teroris. Ketiga, Republika menolak standar ganda negara Barat, terutama AS yang tidak menyebut tindakan teroris karena pelakunya bukan muslim dan tidak berkulit hitam. Keempat, Republika menawarkan definisi terorisme sebagai aksi yang melibatkan penggunaan atau upaya sabotase, pemaksaan, atau kekerasan yang mengakibatkan kematian populasi secara umum. Penelitian ini dapat dijadikan wacana pembentuk kesadaran kritis dalam melawan pandangan negatif pemimpin negara adidaya AS yang sering kali memaksakan makna aksi terorisme dengan Islam dan kaum muslimin.